Shakespeare’s Timeless Legacy: Insights Into Enduring Market-Product Interactions Across Centuries - Suvagondha, Thaweesakdhi (European Scientific Journal, ESJ, 2024)
Shakespeare’s enduring legacy is a testament to his unparalleled ability to engage audiences, a skill evident even during the Bubonic Plague of 1593 when his comedies alleviated societal distress. This article examines how Shakespeare’s strategies have continued to shape market-product interactions, influencing adaptations by British authorities and technological advancements by private enterprises. From the adoption of automatic printing to the transition to digital e-books, and the transformation of plays into movies, television, animation, and interactive games, Shakespearean works have consistently evolved to meet changing consumer preferences. This study aims to provide insights for creating effective product marketing strategies using generative Artificial Intelligence, drawing lessons from the enduring popularity and adaptability of Shakespeare’s works.